Sky full of elephants eaudiobook - Campbell, Cebo (Simon & Schuster Audio, 2024)
"Bold and imaginative." —Tananarive Due "This stunning allegory will spark much discussion." — Publishers Weekly (starred review) "A truly powerful and riveting story." —Booklist In a world without white people, what does it mean to be Black? One day, a cataclysmic event occurs: all of the white people in America walk into the nearest body of water. A year later, Charlie Brunton is a Black man living in an entirely new world. Having served time in prison for a wrongful conviction, he's now a professor of electric and solar power systems at Howard University when he receives a call from someone he wasn't even sure existed: his daughter Sidney, a nineteen-year-old left behind by her white mother and step-family. Traumatized by the event, and terrified of the outside world, Sidney has spent a year in isolation in Wisconsin. Desperate for help, she turns to the father she never met, a man she has always resented. Sidney and Charlie meet for the first time as they embark on a journey across a truly "post-racial" America in search for answers. But neither of them are prepared for this new world and how they see themselves in it. Heading south toward what is now called the Kingdom of Alabama, everything Charlie and Sidney thought they knew about themselves, and the world, will be turned upside down. Brimming with heart and humor, Cebo Campbell's astonishing debut novel is about the power of community and connection, about healing and self-actualization, and a reckoning with what it means to be Black in America, in both their world and ours.